'Cause for Concern'? Policing Black Migrants in Post-War Britain (1945-68). Issue 1 (4th May 2022) - Peplow, Simon
ABSTRACT: This article explores how Black migrants were routinely considered to be a 'cause for concern' in post-war Britain, identified as 'undesirables' and subjected to discriminatory policing practices. Despite the police's professed 'colour-blind' approach of 'non-differentiation' – often raising difficulties or contradictions when called on for their observations – characterisations of Black people as 'more predisposed towards criminality' led to their being disproportionately targeted by the police's discretionary powers. Utilising Home Office and Metropolitan Police Office records, this article demonstrates how the police's professed attempts at liaison with Black communities and recording of 'racial disturbances' were in reality efforts to monitor and 'prove' notions of Black criminality, which, in some cases, led to calls from the police for the mass deportation of so-called 'undesirables'.